2016
DOI: 10.1002/prot.25089
|View full text |Cite
|
Sign up to set email alerts
|

Reactivation of mutant p53: Constraints on mechanism highlighted by principal component analysis of the DNA binding domain

Abstract: Most p53 mutations associated with cancer are located in its DNA binding domain (DBD). Many structures (X‐ray and NMR) of this domain are available in the protein data bank (PDB) and a vast conformational heterogeneity characterizes the various free and complexed states. The major difference between the apo and the holo‐complexed states appears to lie in the L1 loop. In particular, the conformations of this loop appear to depend intimately on the sequence of DNA to which it binds. This conclusion builds upon r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 54 publications
2
18
0
Order By: Relevance
“…Low modes are recognize by long dynamics in proteins 76,77 . Further, PCA reduces the motion in a trajectory 7880 where A set of variables z1, z2…, zp, transformed, called principal components (PCs) are generated. Free Energy Landscape (FEL) 81,82 is applied to calculate the energies of macromolecule conformations sets.…”
Section: Methodsmentioning
confidence: 99%
“…Low modes are recognize by long dynamics in proteins 76,77 . Further, PCA reduces the motion in a trajectory 7880 where A set of variables z1, z2…, zp, transformed, called principal components (PCs) are generated. Free Energy Landscape (FEL) 81,82 is applied to calculate the energies of macromolecule conformations sets.…”
Section: Methodsmentioning
confidence: 99%
“…PCA is carried with long time dynamics by recognizing low modes in proteins [ 28 , 29 ]. PCA reduces and simplifies the complicated movement in long trajectory generated during MD simulation [ [30] , [31] , [32] ]. A transformed set of variables z1, z2…, zp called principal components (PCs) were generated during PCA.…”
Section: Methodsmentioning
confidence: 99%
“…Further evidence of increased stability in the DNA binding interface comes from the increase rigidity observed in S 2 values of N239Y in the latter half of L2, which spans residue 183-194 ( Figure 6 ). Principle component analyses of residue positions in multiple p53 DBD crystal structures have shown this part of L2 to be highly flexible (45). S 2 calculations of WT show that this flexibility is confirmed to be present in WT (32) and N235K but not N239Y ( Figure 6 ).…”
Section: Discussionmentioning
confidence: 99%
“…L1 has been shown to be involved in dynamic DNA binding (37). Principle component analysis (45), molecular dynamics (46, 47), and NMR studies (37) of p53 DBD have shown L1(113-123) to be highly flexible. This flexibility is observed in WT (32) and N235K ( Figure 6 ).…”
Section: Discussionmentioning
confidence: 99%